Literary Correspondence 1965-1982 - Reid, Victor; Manley, Michael; Nettleford, Rex; Miller, Errol; Manley, Edna; Lady Bustamante; Thompson, Dudley; Wynter, Sylvia; Robinson, Leslie; Smith, Jean; Russell Graham; Fitzritson, Donald; et al. (My University, 1965)
A collection of personal and professional correspondence sent to or from Jamaican novelist and cultural leader Victor Stafford Reid between 1965 and 1982. The letters document literary, political, and cultural developments in post-independence Jamaica, including exchanges with Prime Minister Michael Manley and other figures in education and the arts.
116 pgs. Typescript, letter-sized, sepia-toned, in good condition.
Keywords: amaican literature and cultural heritage; Establishment of the Afro-Caribbean Institute of Jamaica; National Trust Commission leadership and cultural policy; Jamaica — Intellectual life — 20th century; Jamaican literature — 20th century — History and criticism; Prime ministers — Jamaica — Correspondence; Norman Manley Award for Excellence — History; Radio Jamaica Limited — History